1978
DOI: 10.1136/adc.53.3.210
|View full text |Cite
|
Sign up to set email alerts
|

Renal scarring and vesicoureteric reflux.

Abstract: (MacGregor and Freeman, 1975; that there is a striking relationship between the incidence of renal scarring and the severity of VUR, and also throw further light on the reputedly rare appearance of new renal scars in patients while under observation. Patients and methodsThe case records and radiographs of all children who attended the renal clinic during 1974 with recently diagnosed or previous UTI have been reviewed.Children with neurological disorders affecting bladder function, e.g. spina bifida, were exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
5

Year Published

1980
1980
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 18 publications
2
33
0
5
Order By: Relevance
“…At present, the most accurate and reliable method for the detection of reflux is conventional voiding cystourethrography, and it should be the first diagnostic study [9,18]. Abnormalities of the upper urinary tract predisposing to, associated with, or aggravating the urinary infection/vesicoureteral reflux complex were correctly identified by sonography in this study, and this has been the experience of others [1 -4].…”
Section: Discussionsupporting
confidence: 56%
“…At present, the most accurate and reliable method for the detection of reflux is conventional voiding cystourethrography, and it should be the first diagnostic study [9,18]. Abnormalities of the upper urinary tract predisposing to, associated with, or aggravating the urinary infection/vesicoureteral reflux complex were correctly identified by sonography in this study, and this has been the experience of others [1 -4].…”
Section: Discussionsupporting
confidence: 56%
“…UU., el Reino Unido e Italia, y las tasas más bajas varían entre el 6% y el 12% en los niños afroamericanos y son del 10% en los niños jamaiquinos. 3,[11][12][13][14] En nuestro país, en un estudio con 300 pacientes, Yılmaz y col. determinaron que la tasa de RVU era del 30,9%. 15 En el estudio actual, se observó que la tasa de RVU coincidía con la bibliografía relevante y que era estadísticamente significativa cuando se analizaron los grupos por separado.…”
Section: Discussionunclassified
“…In addition, the prevalence of VUR in the pediatric age group varies in different countries. Different studies in Western countries found that the prevalence of VUR ranges from 41% and up to 63% (5,19). Interestingly, the lowest VUR prevalence was reported in Black Americans and Jamaicans, indicting racial variations (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Vesicoureteral reflux is the most common congenital abnormalities found in children with recurrent UTI (3,4). Previous studies have found that radiological abnormalities can exist in 25% to 55% of children after their first attack of UTI (5,6). To prevent VUR related sequels, participants can be treated by continuous antibiotic prophylaxis, surgical intervention by ureteric reimplantation, or endoscopic treatment by injecting bulking agents (7).…”
Section: Introductionmentioning
confidence: 99%